Comparative analysis of two editions of the novel "Black Lake" (1929 and 1956) by V. Gzhytskyi (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article attempts to analytically compare two editions of the «Black Lake» by V. Gzhitskogo the 1929 and the 1956 editions. A number of author's «improvements» and changes on the basis of the modern discourse were discovered, that as a result of which, the writer took ownership, and reworked a series of episodes, which affected the quality of its artistic value.
Keywords: novel; genre narrating discourse; narrator; chauvinism; ideology